Uniaxial tensile properties of TiO2 coated single wool fibers by sol-gel method: The effect of heat treatment - Aksakal, Baki; Koc, Kenan; Bozdogan, Altan; Tsobkallo, Katherina (WILEY, 2013)
Single wool fibers were coated with (2) by using the sol-gel method. (2) coated single wool fibers heated at different temperatures from 25 to 200 degrees C were investigated and compared with those of uncoated single wool fibers. It was observed that the shape of the stress-strain curve of (2) coated wool fibers became the same as uncoated wool fibers and showed a similar tendency of change to uncoated wool fibers with increasing temperature. But, the (2) coated wool fibers obtained higher rigidity than uncoated wool fibers and up to their rupture points; they obtained higher stress levels in three deformation regions in the stress-strain curves, which indicates stronger wool fibers. Although the breaking extension of (2) coated wool fibers decreased little by about 8%, the Young's modulus of (2) coated wool fibers increased significantly by 19%, which was caused mostly by an increment in the stiffness of the cuticle layer of the wool fiber, and remained relatively higher than that of uncoated wool fibers after heat treatments. Structural changes in both uncoated and (2) coated single wool fibers due to thermal effect, which caused the changes in the uniaxial tensile properties and the thermal behaviors of these fibers were discussed by using spectroscopic and thermal analysis methods in detail. (c) 2013 Wiley Periodicals, Inc.
Keywords: mechanical properties; thermal properties; fibers; KERATIN FIBERS; SPECTROSCOPY; ACID; TRANSFORMATION; TEMPERATURE; HAIR; Polymer Science